Chapter 15 The Use and Abuse of Moral Preferences in the Ethics of Self-Driving Cars - Paulo, Norbert (Taylor & Francis, 2024)
In this contribution, it is argued for the potential of empirical moral philosophy in the context of the regulation of self-driving cars. This chapter focuses on the use and abuse of capturing the moral preferences of the general public and including these in the regulatory process. The Moral Machine Experiment is used as an example of collecting evidence on public moral preferences to help program self-driving vehicles. After a comprehensive presentation of the aim and methodology of the study, criticisms are discussed and partly refuted.  It is concluded that the findings of the Moral Machine experiment are an impressive collection of data that has indeed contributed to the ethical and legal debate of how to regulate moral dilemmas caused by self-driving cars. Future empirical research in the field can continue along these lines. While the methodological limits of the Moral Machine experiment have to be acknowledged, it is nevertheless important to consider public moral preferences in the ethics of self-driving cars.